2007
DOI: 10.1002/pamm.200700761
|View full text |Cite
|
Sign up to set email alerts
|

Hypertumors in cancer can be caused by tumor phosphorus demand

Abstract: In cancer, tumoral and peritumoral environmental conditions are controlled mostly by the unusual metabolism of malignant cells. For example, tumors typically demand much more phosphorus (P) than normal tissue does, primarily because tumor cells upregulate ribosome biogenesis. Here I use mathematical models to show that this unusual demand for P can lead to a hypertumor, which is a region of highly aggressive cells growing parasitically on the original tumor that can kill all or part of it. Previous work has su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The evolution of carrying capacity has largely been disregarded in models of tumor growth, which have instead focused on increased growth rates and adaptation to adverse environmental conditions (low nutrients, cytotoxic therapy etc.). A notable exception is the work of Nagy [23,24], in which the niche construction dilemma in the context of cancer has been investigated. Using a system of ordinary differential equations that captures the dynamics of cancer cells, immature blood vessels and fully formed vessels he showed that a resident cancer cell population can be invaded by a mutant that invests less in attracting blood vessels and more in proliferation, eventually leading to 'evolutionary suicide'.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of carrying capacity has largely been disregarded in models of tumor growth, which have instead focused on increased growth rates and adaptation to adverse environmental conditions (low nutrients, cytotoxic therapy etc.). A notable exception is the work of Nagy [23,24], in which the niche construction dilemma in the context of cancer has been investigated. Using a system of ordinary differential equations that captures the dynamics of cancer cells, immature blood vessels and fully formed vessels he showed that a resident cancer cell population can be invaded by a mutant that invests less in attracting blood vessels and more in proliferation, eventually leading to 'evolutionary suicide'.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Second, tumors are known to be phosphorus-demanding due to the increased ribosomal biogenesis in malignant cells, which requires a high amount of phosphorus. 36 Clusters of high phosphorus signals of similar intensity to that of the talc particulates can be noted across the section ( Figure 3 , panel F). Interestingly, the distribution of the Fe signal appeared to be significantly increased around the talc deposits and in between clusters of these magnesium-rich particulates.…”
Section: Resultsmentioning
confidence: 77%
“…Moreover, high levels of Na can be associated with necrotic areas with poor vascularization, characteristic to the tumor microenvironment . Second, tumors are known to be phosphorus-demanding due to the increased ribosomal biogenesis in malignant cells, which requires a high amount of phosphorus . Clusters of high phosphorus signals of similar intensity to that of the talc particulates can be noted across the section (Figure , panel F).…”
Section: Resultsmentioning
confidence: 97%
“…The idea of a hypertumour was first raised in 2004 when Nagy modelled tumour behaviour as a function of an ecological community 106 . He later expanded the model to identify two causes that could lead to the development of a hypertumour within the original tumour: insufficient angiogenesis leading to the 'hijacking' of existing vascular infrastructures within the tumour by cells that themselves produce insufficient amounts of tumour angiogenic factors 70 , and an increased demand for phosphorus, leading to an up-regulation of phosphate transport proteins and, thus, upregulated ribosome biogenesis 107 . While the hypertumour model certainly solves some problems raised by Peto's paradox - and indeed, cancer cells have been identified that compete with other populations of malignant cells 105 - one should bear in mind that tumour size, i.e.…”
Section: Novel Protection Mechanisms Against Cancermentioning
confidence: 99%